Pengaruh pemberian telur ayam rebus dan tablet tambah darah terhadap peningkatan kadar hemoglobin pada remaja putri - Indah Trianingsih; Marlina Marlina; Yusari Asih; Nelly Indrasari; Shindy Bella Aulia (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Anemia among adolescent girls in Indonesia remains quite high. If left untreated, anemia in adolescents will persist into adulthood and significantly contribute to maternal mortality, premature birth, and low birth weight. Anemia in adolescents causes fatigue, decreased concentration, low academic achievement, and can reduce immunity. Purpose: To determine the effect of providing boiled chicken eggs and iron supplements on increasing hemoglobin levels in adolescent girls. Method: The study design used a quasi-experimental approach with a one-group pretest-posttest design. The sampling technique used a purposive sampling technique, with 18 adolescent girls. The treatment group was given boiled chicken eggs and iron supplements. The study period was 14 full days. Data analysis used a paired t-test. Results: This study showed that 13 respondents (72.2%) were anemic before the administration of boiled chicken eggs and iron supplements. After the administration of boiled chicken eggs and iron supplements, 2 respondents (11.1%) were anemic. The statistical test result showed a p-value of 0.000 <0.05. Conclusion: There is an effect of giving boiled chicken eggs and iron tablets on increasing hemoglobin levels in adolescent girls. Keywords: Adolescent Girls; Chicken Eggs; Hemoglobin; Iron Tablets Supplementation. Pendahuluan: Anemia pada remaja putri di indonesia masih cukup tinggi. Anemia pada remaja jika tidak tertangani akan berlanjut hingga dewasa dan berkontribusi besar terhadap AKI, bayi lahir prematur, dan bayi berat lahir rendah. Anemia pada remaja menyebabkan lekas lelah, konsentrasi belajar menurun, prestasi belajar rendah dan dapat menurunkan daya tahan tubuh. Tujuan: Untuk mengetahui pengaruh pemberian telur ayam rebus dan tablet tambah darah terhadap peningkatan kadar hemoglobin remaja putri. Metode: Desain penelitian menggunakan quasi eksperiment dengan pendekatan one group pretest posttest design. Teknik pengambilan sempel menggunakan purposive samping, sampel digunakan sebanyak 18 remaja putri. Kelompok perlakuan diberikan telur ayam rebus dan tablet tambah darah. Waktu penelitian ini adalah selama 14 hari penuh. Uji analisis data menggunakan Paired t-test. Hasil: Peneltian ini menunjukkan bahwa sebelum pemberian telur ayam rebus dan tablet tambah darah anemia 13 responden (72.2%). Sesudah pemberian telur ayam rebus dan tablet tambah darah anemia 2 responden (11.1%). Hasil uji statistik p value sebesar 0.000 <0.05. Simpulan: Ada pengaruh pemberian telur ayam rebus dan tablet tambah darah terhadap peningkatan kadar hemoglobin pada remaja putri. Kata Kunci: Hemoglobin; Remaja Putri; Tablet Tambah Darah; Telur Ayam.